The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7717/peerj.10007
|View full text |Cite
|
Sign up to set email alerts
|

Quinquelaophonte enormissp. nov., a new interstitial copepod (Harpacticoida: Laophontidae) from Korea

Abstract: We collected an undescribed laophontid copepod from a coarse sand habitat on the east coast of Korea and named it Quinquelaophonte enormis sp. nov. We compared the detailed morphological characteristics of the new species with those of congeneric species. Among them, the new species shows a superficial resemblance to the Californian species Quinquelaophonte longifurcata Lang, 1965. However, the two species are easily distinguishable by the setation of the syncoxa on the maxilliped and the fourth swimming leg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…However, due to the limited available information, it is premature to suggest a phylogeographic history and evolutionary relationships among the examined species. However, we noticed that Q. enormis is geographically closer to the new species (Republic of Korea [17]) than Q. aurantius, which was reported from the opposite hemisphere (New Zealand [9]). In Korean fauna, in addition to these two species, there is one more species, Q. koreana, which is intuitively distinguishable (e.g., short caudal rami, two setae on the exopod of the antenna, two inner setae on the P3 exp-3 in both sexes, four armatures on the distal endopal segment of the P4 in both sexes, and the shape of the female P5) and was reported from the coast of the Yellow sea [16].…”
Section: Molecular Data and Phylogenymentioning
confidence: 49%
See 3 more Smart Citations
“…However, due to the limited available information, it is premature to suggest a phylogeographic history and evolutionary relationships among the examined species. However, we noticed that Q. enormis is geographically closer to the new species (Republic of Korea [17]) than Q. aurantius, which was reported from the opposite hemisphere (New Zealand [9]). In Korean fauna, in addition to these two species, there is one more species, Q. koreana, which is intuitively distinguishable (e.g., short caudal rami, two setae on the exopod of the antenna, two inner setae on the P3 exp-3 in both sexes, four armatures on the distal endopal segment of the P4 in both sexes, and the shape of the female P5) and was reported from the coast of the Yellow sea [16].…”
Section: Molecular Data and Phylogenymentioning
confidence: 49%
“…We confirmed that these Quinquelaophonte individuals were conspecific and distinct from congeners using an integrative approach, including morphological and genetic data. The discovery of the new species is the third in the Northwest Pacific, following Q. koreana (Taean, Republic of Korea [16]) and Q. enormis (Busan, Republic of Korea [17]). Moreover, we inferred the phylogenetic relationships among the new species and two congeners (Q. aurantius and Q. enormis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The family Laophontidae T. Scott, 1905 is essentially marine, free-living and benthic, mainly inhabiting the intertidal zone or shallow subtidal habitats and is commonly found amongst algae and seagrass ( Huys et al 1996 , Boxshall and Halsey 2004 , Kaymak and Karaytuğ 2014 ). Additionally, the Laophontidae is a very large and diverse family containing more than 320 species and 74 genera in the Harpacticoida ( Huys and Lee 2018 , Kim et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%